Estudo genômico e transcritômico de isolados selecionados de alto rendimento de dorna de fermentação alcoólica de Saccharomyces cerevisiae - Lourencetti, Natália Manuela Strohmayer [UNESP] (2014)
Brazil currently has an estimated production of bioethanol with crop 2013/14 from 27.17 billion liters. This production is derived from a fermentation process of Brazilian sugarcane mills and is characterized today as a semi-continuous process. The yeast Saccharomyces cerevisiae is the most comprehensive in fermentation processes, by being adaptable to different environments, having a rich diversity of phenotypic and genotypic profiles, showing that the interactions between environmental factors and influences in this organism identification of essential and specific features in the fermentative process. The construction of a bank of organisms related to ethanol production is vital to the interests of researchers Bioen UNESP program. Thus, it is fundamental to the existence of a collection of yeast strains with high fermentation potential. In a previous study conducted by our group, were selected from a Brazilian plant two strains (ZFC4 and ZFD4) with potentially differential characteristics in the ethanol production process. Based on these data, the aim of this study was first to analyze genotypic and phenotypic characteristics of strains ZFC4 and ZFD4 to identify functional genetic factors through sequencing DNA and RNA global new generation HiSeq Ilumina and subsequently selected strains were screened for combinations with industry standards (PE-2, CAT and SA-I), aiming at selecting promising synergistic associations in the fermentation process for the alcohol sector. For both the associations of these strains were evaluated for cell growth, assimilation of sugars, tolerance to temperature and ethanol and fermentative capacity. All combinations made between the patterns and ZFC4 and ZFD4 strains were synergistic for all parameters analyzed, especially in relation to resistance to high ethanol concentrations and temperature. Importantly, our lines alone were as effective as the fermentation patterns, however these in combination ...